2023
DOI: 10.1002/adfm.202304929
|View full text |Cite
|
Sign up to set email alerts
|

Integration Plasma Strategy Controlled Interfacial Chemistry Regulation Enabling Planar Lithium Growth in Solid‐State Lithium Metal Batteries

Abstract: Solid‐state lithium metal batteries (SSLMBs) are identified as a highly promising candidate for next‐generation energy storage devices, yet they still face uncontrollable dendritic lithium (Li) growth originating from interfacial incompatibility. To address this issue, an “integration plasma (IP)” strategy for interlayer construction is proposed that integrates metal reduction and vapor deposition functions, featuring the ability to give a manipulable and quantifiable chemical regulation for controlling the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…Sun et al [38] reported an "integration plasma (IP)" strategy for constructing an interlayer layer between Li anode and SSE (Fig. 4a).…”
Section: Vapor Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al [38] reported an "integration plasma (IP)" strategy for constructing an interlayer layer between Li anode and SSE (Fig. 4a).…”
Section: Vapor Depositionmentioning
confidence: 99%
“…Moreover, the high mechanical stiffness of inorganic SSEs can significantly increase the stress/strain at the electrode/electrolyte interface and is inadequate to accommodate the volumetric expansion during cycling, thereby leading to high interfacial resistance [37]. Introducing a buffer/protective layer between the electrodes and the electrolytes is one of the effective strategies to enhance the physical contact and to regulate the Li/SSE interface [31,[38][39][40][41]. For instance, the deposition of ZnO layer on the surface of garnet-like Ta-doped LLZO via atomic layer deposition significantly improved the wettability of the garnet SSE to Li anode, resulting in a conformal contact without interfacial void space [42].…”
Section: Introductionmentioning
confidence: 99%
“…Shiyi Sun et al 88 proposed an “integration plasma (IP)“ strategy that combines the functionalities of metal reduction and gas-phase deposition. This strategy offers an operable and quantifiable chemical control to regulate the surface concentration and atomic ratio of metal and electronegative elements introduced onto the solid electrolyte.…”
Section: Plasma Application For Energy Storage Materialsmentioning
confidence: 99%
“…1a), which hampers Li + transportation and fails to block the electron transfer. 19 The continuous growth of the SEI layer leads to uneven Li + /e − flux, resulting in increased interfacial resistance and local current density (hotpots). 20 The presence of hotspots and volume changes further exacerbates the interfacial chemistry, promoting the growth of lithium dendrites and ultimately causing cell short-circuiting.…”
Section: Introductionmentioning
confidence: 99%